2012
DOI: 10.3109/03630269.2012.709896
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Hb Paksé (codon 142, TAA>TAT,α2) and its Combinations in Patients also Carrying Hb Constant Spring (codon 142,TAA>CAA,α2) in Northern Thailand

Abstract: The incidence of Hb Paksé (codon 142, TAA>TAT, α2) might have been underestimated due to misidentifying some cases as Hb Constant Spring (Hb CS, codon 142, TAA>CAA, α2) since both abnormal hemoglobins (Hbs) migrate to the same position on Hb electrophoresis or chromatography. Multiplex asymmetric allele-specific polymerase chain reaction (PCR) for identification of Hb CS and Hb Paksé, and a real-time PCR (ReTi-PCR) with SYBR Green1 high resolution melting (HRM) analysis, for detection of the α-thalassemia-1 (α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Hb Paksé and its combinations with aand b-thal had been reported in northern Thailand (25). However, in the current study there were no samples carrying Hb Paksé.…”
mentioning
confidence: 65%
“…Hb Paksé and its combinations with aand b-thal had been reported in northern Thailand (25). However, in the current study there were no samples carrying Hb Paksé.…”
mentioning
confidence: 65%
“…It not only could reduce the contamination risk, but also could be applied for high-throughput mutation scanning on genes for which large cohorts of patients has to be investigated. As early as 2008, Pornprasert S et al diagnosed some deletion forms and a few mutations of thalassemia by HRM analysis in Thailand successfully [9], [24], [25]. Recently, it has been used in the detection of β-thalassemia mutations in Chinese, but interference of SNP and Hb variants was still an embarrassment [10], [11].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity and specificity of HRM for mutation detection are extremely high, and this technique also has the advantages of low cost and high throughput. Recently, this technique has also been used in the detection of α- and β-thalassemia [9], [10], [11], but there is no systemic study on the diagnostic capability of HRM to identify β-thalassemia. In the previous reports, the major interference was the SNP in hemoglobin-β gene such as rs713040, rs10768683 and rs1609812, which reduced the accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular screening in selected populations in Thailand found HbCS to be approximately 10 times more prevalent than Hb paksé (5%‐5.8% vs 0.5%‐1.5%) . One study found Hb Paksé and its combinations, including compound HbCS/Hb Paksé, in 4.4% of patients who were previously diagnosed as HbCS . This present report underlines the importance of DNA analysis in patients who have been diagnosed as HbCS from electrophoresis or HPLC.…”
Section: Laboratory Parametersmentioning
confidence: 50%